Dynamic analysis of composite beam with piezoelectric layers under thermo-mechanical load - Toudehdehghan, Abdolreza*; Rahman, M. M.; Farrukh, Nagi (IOP Publishing, 2017)
In this paper, the control of composite beam vibrations with sensor and actuator connected layers is considered with consideration of the effect of thermal environment. The coupling relation between electrical field and mechanical deformation with uncoupled thermal impact are used. The mathematical model of shear deformation (Timoshenko’s theory) has been applied and basic equations for piezoelectric sensors and actuators have been proposed. The equation of motion for the beam structure is obtained by the Hamilton principle and analyzed by finite element method. The control algorithm is based on proportional velocity control. Hence, the purpose of this article is to investigate the direct and inverse effects of piezoelectric on control of simply supported beam vibration under uniform temperature.